NEW WORLD OUTLOOK IN THE LIGHT OF THE WESTERNIZATION OF PETER I - T. V. Chernikova (Vestnik MGIMO-Universiteta)
The reign of Peter I paradoxically combined both the apogee of the might of the old patrimonial state and the accelerated westernization of the country. The article briefly analyzes some of the factors that strengthened the state patrimonial system: the consequences of the decree on the Unified Heritage of 1714 and the expansion of serfdom due to the appearance of new categories of serfs.To a greater extent, the article is devoted to the study of accelerated Westernization in Russia under Peter the Great. It resulted in the curtailment of the patrimonial way of life in Russia.The article focuses on the emergence of a new worldview doctrine. It considers various forms through which the formation of new understandings of social structures, culture, system of power and life in general took place. Such new practices as uttering panegyrics in honor of the monarch and his policies, public celebration of military victories (the organization of the so-called «Triumphs») and the church reforms greatly contributed to the formation of the new worldview. One of the vivid figures exemplifying it was Theophan Prokopovich.In the first quarter of the 18th century westernization came to Russia directly from Western Europe. It removed all barriers to direct communication between Russians and foreigners, discredited the old ecclesiastical postulate that all Western Christians were “heretics”, paved the way for the beginning of internal modernization as well as for the tragic fate of the socio-cultural split in Russia between the upper educated social strata and the bulk of the Russian population that remained in the Middle Ages.